TOPOLOGIYA ELEMENTLERIN OQÍTÍW USÍLLARÍ - Qaypnazarova, G.X. (SCIENCE and SOCIETY, 2024)
In this article, is the practical aspect of helping students of pedagogical universities to acquire practical skills in topology, teaching methods and the importance of the topology course.